Strong normalization for first-order logic - Tigran M. Galoyan (Изд-во НАН РА)
In this paper we discuss strong normalization for the ! 8 - fragment of first - order logic. The use of the method of collapsing types to transfer the result concerning strong normalization (that is, any derivation r is strongly normalizable) from implicational logic to ¯rst-order logic is illustrated (ref [1]). The considered result is improved by a complement, which states that for any derivation r and its collapse r c we need the same number of one-step reductions (the !1 rule) to bring them to their normal forms.
Keywords: Mathematics